Heart Failure after Laboratory Confirmed Influenza Infection (FLU-HF). Issue 1 (23rd June 2022) - Sin, Phyllis; Siddiqui, Muhammad; Wozniak, Rashell; Bare, Idris; Minion, Jessica; Sanche, Stephen; Udell, Jacob; Lavoie, Andrea; Dehghani, Payam
Background: Influenza has been shown to exacerbate heart failure (HF). Importantly, no study to date has examined the relationship between HF hospitalizations (HFH) with laboratory confirmed influenza infections. This study evaluated the association between laboratory confirmed influenza infection and HFH in the two largest hospitals in Saskatchewan, Canada. Methods: We used a retrospective self-controlled case series design to evaluate the association between laboratory-confirmed influenza infection and HFH. We compared the incidence ratio for HFH during the influenza risk interval with the control interval. We defined the influenza risk interval as the seven days after a laboratory confirmed influenza result and the control interval as one year before and after the risk interval. Results: We identified 114 HFH that occurred within one year before and after a positive test result for influenza between April 1, 2010, and April 30, 2018. Of these, 28 (28 admissions per week) occurred during the risk interval and 86 (0.853 admissions per week) occurred during the control interval. The incidence ratio of a HFH during the risk interval as compared with the control interval was 33.53 (95% confidence interval [CI], 21.89 to 51.36). A decline in incidence was observed after day seven; between days 8 to 14 and 14 to 28 incidence ratios was 0.91 (95% CI, 0.13 to 6.52) and 0.91 (95% CI, 0.22 to 3.68) respectively. Conclusion: We have observed a significant association between acute influenza infection and HFH. However, further research with a larger sample size and involving a multicenter setting is warranted. Highlights: Influenza may contribute and exacerbate heart failure events especially during annual influenza season. Early identification of influenza among patients with heart failure, could lead to earlier treatment with antiviral medication, reduce unnecessary antibiotic use, and tail off the morbidity and mortality. In this study, despite our efficient study design, our sample size was limited to only the two largest hospitals in the province, possibly excluding a significant population in remote areas.